GENETIC DIVERSITY IN LOCAL BORO RICE (Oryza sativa L.) GENOTYPES OF BANGLADESH (Bangladesh Journal of Plant Breeding and Genetics, 2013)
Genetic diversity in 40 traditional boro rice genotypes was studied under irrigated condition through Mahalanobis D2 statistic for grain yield and yield contributing characters. The genotypes were grouped into five clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster IV contained the highest number of genotypes (22) and the cluster II and V contained the lowest (1). The highest intra-cluster distance was noticed for the cluster III and lowest for cluster II and V. The highest inter-cluster distance was observed between cluster II and III followed by cluster II and V, cluster I and II and the lowest between cluster I and IV. Regarding inter-cluster distance, the genotypes of cluster II   showed high genetic distance from all other clusters. The genotypes from cluster II could be hybridized with the genotypes of other clusters for producing transgressive segregants. Based on positive value of vector 1 and vector 2, panicle/hill had maximum contribution towards genetic divergence. The highest cluster means for yield, flag leaf length and grain length breadth ratio were obtained from cluster IV. The highest 1000-grain weight, shortest growth duration and grain breadth were found in cluster II while the lowest mean value for yield, flag leaf length, filled grains and 1000 grain weight were found in cluster V.  Therefore, more emphasis should be given on cluster II, III and cluster IV for selecting genotypes as parents for crossing with the genotypes of cluster V which would be used to produce new recombinants with desired traits.DOI: http://dx.doi.org/10.3329/bjpbg.v26i1.19980